2020
DOI: 10.1002/jsfa.10443
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and comparison of seed protein, oil, and sugars in edamame dried using two oven‐drying methods and mature soybeans

Abstract: BACKGROUNDEdamame, a vegetable soybean (Glycine max) grown mainly in Asia, has high nutritional and market value and is a relatively new crop to North America. By 2 years of field trials, we evaluated the seed composition traits in 54 genotypes to analyze the differences and relationship between edamame seeds dried by two oven‐drying methods and mature soybeans.RESULTSThe genotypic differences were significant for all the traits investigated. Significant differences also existed between the two sets of dried e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 43 publications
6
24
0
1
Order By: Relevance
“…In addition, the two‐year averages of oleic and linoleic acid contents in the unshelled–dried edamame were slightly larger than those in the shelled–dried edamame. The changes of oleic and linoleic acid contents were consistent with those of seed oil content 22 . This is reasonable as of the five major components of oil in soybean, oleic and linoleic acids contribute the most proportion of the total oil, approximately 20–30% and 50–60% in commercial soybean, respectively 1,35–37 …”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…In addition, the two‐year averages of oleic and linoleic acid contents in the unshelled–dried edamame were slightly larger than those in the shelled–dried edamame. The changes of oleic and linoleic acid contents were consistent with those of seed oil content 22 . This is reasonable as of the five major components of oil in soybean, oleic and linoleic acids contribute the most proportion of the total oil, approximately 20–30% and 50–60% in commercial soybean, respectively 1,35–37 …”
Section: Resultssupporting
confidence: 78%
“…The result indicated that the concentrations of seed fatty acids in the edamame were more influenced by the external factors than those in mature soybean. In other words, selection for seed fatty acids in mature soybean would be more effective than in edamame, a finding consistent with the seed oil content 22 . Higher estimates of broad‐sense heritability in the range 0.69–0.97 for fatty acids were reported in commercial mature soybeans 37,47,48 .…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations